Encyclopedia of hinduism - Cush, Denise; Robinson, Catherine; York, Michael (Routledge, 2007)
Covering all aspects of Hinduism, this encyclopedia includes more ethnographic and contemporary material in contrast to the exclusively textual and historical approach of earlier works
Keywords: Wörterbuch; Hinduismus